The peopling of the Muri Mountains, Northern Nigeria:: evidence from linguistics and ethnography - Adelberger, Jörg; Blench, Roger (AAeO - Afrikanistik-Aegyptologie-Online, 2026)
The Muri Mountains and the adjacent area of Northern Nigeria is home to a complex mosaic of ethnic groups whose languages are from different language families (Chadic, Adamawa, Jarawan Bantu, Jukunoid, Central Sudanic) as well as including an isolate, Jalaa. The paper synthesises both detailed work on a large corpus of historical traditions recorded in the 1990s, supplemented by reference to published and unpublished sources. This has numerous parallels to the situation in other ‘refuge’ areas of Africa, most notably the Nuba Mountains. An outline of the complex population history is presented with hypotheses as to the stratification of populations and the dynamic flux and migrations of peoples. The language isolate, Jalaa, may well be the remaining evidence for the earliest layer of population. The first incoming population was probably the Adamawa speakers, followed by Chadic groups. The Jarawan Bantu and the Jukun would have been later and the Kaba Laka, Central Sudanic, the final migration into the area. The ethnography of the region is characterised by exchange of ideas and practices, as well as linguistic and cultural restructuring. In contrast to other areas of Africa, the Muri Mountains have remained almost unknown to the broader research community.
Keywords: Muri mountains; Nigeria; Northern Nigeria; ethnic groups; history; Afroasiatic; Niger-Congo; language isolates; Chadic; Adamawa; Jarawan Bantu; Jukunoid; Central Sudanic; Jalaa; migration